2020
DOI: 10.31235/osf.io/4sfrj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating the microscopic effect of brushing stone tools as a cleaning procedure

Abstract: Cleaning stone tool surfaces is a common procedure in lithic studies. The first step widely applied at any archaeological site (and/or at field laboratories) is the gross removal of sediment from the surfaces of artifacts. Lithic surface alterations due to mechanical action applied in wet or dry cleaning regimes have never been examined at a microscopic scale. This could have important implications in traceology, as any modern surface modifications inflicted on archaeological artifacts might compromise their f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…A previous study on experimentally worked bone surfaces found a similar pattern associated with duration of use when bones were worn against fresh animal skin, a supple, sticky material that readily incorporates external particles adding to its abrasiveness 48 . Another experimental study testing the effects of cleaning procedures on stone tools also found an increase in this surface texture parameter after rubbing dirt off of a flint flake for about 1 min 65 . As with fresh skin and sediment particles, this increase in Smrk1 indicates that eraser use causes alterations to the highest portion of bone surfaces resulting in the plateauing of the microtopography at the µm-scale.…”
Section: Discussionmentioning
confidence: 89%
“…A previous study on experimentally worked bone surfaces found a similar pattern associated with duration of use when bones were worn against fresh animal skin, a supple, sticky material that readily incorporates external particles adding to its abrasiveness 48 . Another experimental study testing the effects of cleaning procedures on stone tools also found an increase in this surface texture parameter after rubbing dirt off of a flint flake for about 1 min 65 . As with fresh skin and sediment particles, this increase in Smrk1 indicates that eraser use causes alterations to the highest portion of bone surfaces resulting in the plateauing of the microtopography at the µm-scale.…”
Section: Discussionmentioning
confidence: 89%
“…To date, ML has been applied in a number of lithic studies addressing a wide variety of anthropological questions: identifying heat-treated raw material nodules, a practice employed to improve the ease of working raw nodules into stone artifacts [15]; identifying the materials worked by a stone tool according to the classification of the use-wear created on its edge [16], [17]; predicting the original flake mass from variables on the striking platform in order to quantify the degree of resharpening (and thus the length of its use-life as a tool) [18]; predicting site formation conditions from the surface alteration of the site's lithic artifacts [19]; creating more quantitatively rigorous approaches to the creation of typologies for studying artifact shape through time and space [20], [21]; predicting the raw material of the stone tool from the cut marks produced by the edge [22]; identifying the geochemical signatures of geological sources of lithic raw materials as a means of studying prehistoric mobility and material selection criteria [23], [24]; distinguishing the flake products from different reduction strategies for exploiting the volume of a core [25]; distinguishing chronological manifestations of lithic behavior between the Middle and Late Stone Age in Africa through the presence vs. absence of types within assemblages [26]; developing virtual knapping software [27]; and quantifying lithic knapping skill acquisition for studying the evolution of human cognition [28].…”
Section: B Lithic Technologymentioning
confidence: 99%
“…Due to the difficulty interpreting the t-SNE embedding, the "outliers" removed could in fact be valid datapoints that are simply difficult to classify, thereby artificially increasing accuracy scores. In [16] missing data was filled in with the median of the features from its class.…”
Section: A Train/test Contaminationmentioning
confidence: 99%